TNI Guarding the Prosecutor's Office Considered in Line with Prabowo's Asta Cita - A. Junaedi Karso (International Forum of Researchers and Lecturers, 2025)
The deployment of TNI soldiers has sparked controversy due to concerns over the strengthening of militarism in civilian institutions. This action has raised alarm among various human rights groups and political analysts who argue that it undermines the democratic principles of civilian control over military forces. The Attorney General's Office (AGO), the TNI, and the Chief of Police have publicly addressed the issue, especially the deployment of TNI soldiers to guard the AGO Complex, as well as the High Prosecutors' Offices (Kejati) and District Prosecutors' Offices (Kejari) across Indonesia. The order for this deployment was issued in the TNI Commander’s Telegram Number TR/442/2025 on May 6, 2025. This order is part of a broader effort to increase security at critical state institutions, especially in light of recent security threats. The deployment of soldiers is part of a follow-up to the cooperation agreement between the TNI and the AGO, which was formalized in the Memorandum of Understanding NK/6/IV/2023/TNI dated April 6, 2023. The agreement outlines eight points of cooperation, which include: (1) Education and training for TNI personnel in law enforcement procedures; (2) Exchange of information for law enforcement purposes, ensuring better collaboration between the military and civilian law enforcement agencies; (3) The assignment of TNI soldiers to assist in guarding AGO facilities and other law enforcement offices; and (4) Other security-related assistance, such as providing military expertise to ensure the integrity and safety of AGO operations. While the cooperation between the TNI and AGO is framed as an effort to enhance security and operational efficiency, critics argue that this deployment could lead to the militarization of civilian functions, potentially causing conflicts of interest and compromising the impartiality of the judicial system.